2014
DOI: 10.1590/s0100-204x2014000600009
|View full text |Cite
|
Sign up to set email alerts
|

Biometric analysis of protein and oil contents of soybean genotypes in different environments

Abstract: The objective of this work was to identify by biometric analyses the most stable soybean parents, with higher oil or protein contents, cultivated at different seasons and locations of the state of Minas Gerais, Brazil. Forty-nine genotypes were evaluated in the municipalities of Viçosa, Visconde do Rio Branco, and São Gotardo, in the state of Minas Gerais, from 2009 to 2011. Protein and oil contents were analyzed by infrared spectrometry using a FT-NIR analyzer. The effects of genotype, environment, and genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
(28 reference statements)
1
11
0
1
Order By: Relevance
“…On average for all six environments, PC was negatively correlated with GY (r = −0.74**), whereas the association between OC and GY (r = 0.34), and between oil and protein contents (r = −0.09) were not significant. These associations are present in wheat, but also in other crops [37,[49][50][51] which makes it difficult to develop productive cultivars with high contents of protein and oil [52]. In our study, cvs.…”
Section: Genotypic Variationsmentioning
confidence: 74%
See 1 more Smart Citation
“…On average for all six environments, PC was negatively correlated with GY (r = −0.74**), whereas the association between OC and GY (r = 0.34), and between oil and protein contents (r = −0.09) were not significant. These associations are present in wheat, but also in other crops [37,[49][50][51] which makes it difficult to develop productive cultivars with high contents of protein and oil [52]. In our study, cvs.…”
Section: Genotypic Variationsmentioning
confidence: 74%
“…Rodrigues et al [52] reported that water stress and high temperatures reduce both protein and oil contents in soybean seeds, while Rotundo and Westgate [57] concluded that temperature has a more pronounced effect on oil content, but it also affects protein content. Barbosa et al [58] found that higher temperatures during grain filling favored oil accumulation in soybean.…”
Section: Ge Effects On Oc Pc and Gymentioning
confidence: 99%
“…The parameters of adaptability and stability contribute to management adjustments and better recommendation of cultivars. This is observed in species of agricultural interest, such as corn for grain production (Cargnelutti Filho et al, 2007), oat for the content of betaglucan (Crestani et al, 2010) and soybean for oil and protein contents in the seeds (Rodrigues et al, 2014). Table 3.…”
Section: Resultsmentioning
confidence: 94%
“…Outros autores também relatam variabilidade do teor de proteína e óleo em soja. Rodrigues et al (2014), em estudo com 49 genótipos, relatam teores de proteína entre 32,07 e 48,57% e, de óleo, entre 14,40 e 24,20%. Quanto à divergência genética, as distâncias genéticas estimadas entre os 29 genótipos do Grupo 1 variaram entre 0,04 e 0,85 e apresentaram média de 0,57.…”
Section: Resultsunclassified